Analisis Hukum Tindak Pidana Aborsi di Kecamatan Tanjung Morawa (Studi di Kantor Kepolisian Resort Kota Deli Serdang) - Juliandi Juliandi; Talita Syamantha; Chairus Suriyati; Junaidi Lubis (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
Abortion is criminal act. So that in law enforcement, the village, sub-district and so on governments should also be involved in providing information about the dangers of abortion crimes, especially to families and young generations in Tanjung Morawa District. Abortion crimes that occurred in Tanjung Morawa District, Deliserdang Regency also increased from the previous 15 incidents in 2022 and around 28 incidents until 2025. Of course, this criminal act of abortion must be carried out by law enforcement so that in the future the same criminal act will not be repeated in the future. Many individuals commit the crime of abortion secretly, and most of them are assisted by people who do not have adequate training. The obejctives of the research include to enforce criminal law for every abortion perpetrator, especially in Tanjung Morawa District. The topic was chosen because of a sense of concern in the people of Tanjung Morawa to be more responsible and not to have abortions for various specific reasons. Combinations normative and empirical to describe and explain events from various reference sources and the study's findings, which included interviews with members of the Deliserdang Resort police, revealed that the dread of becoming pregnant outside of marriage led to a number of criminal abortions, having free sex, and lack of responsibility from the male side. With this research, in the future the crime of abortion can be minimized in Tanjung Morawa sub-district.